2016
DOI: 10.1038/srep38690
|View full text |Cite
|
Sign up to set email alerts
|

Set anode potentials affect the electron fluxes and microbial community structure in propionate-fed microbial electrolysis cells

Abstract: Anode potential has been shown to be a critical factor in the rate of acetate removal in microbial electrolysis cells (MECs), but studies with fermentable substrates and set potentials are lacking. Here, we examined the impact of three different set anode potentials (SAPs; −0.25, 0, and 0.25 V vs. standard hydrogen electrode) on the electrochemical performance, electron flux to various sinks, and anodic microbial community structure in two-chambered MECs fed with propionate. Electrical current (49–71%) and CH4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…showing that a direct electrooxidation of proprionate is possible. On the other hand, Hari et al (2016) suggested that current from propionate would be generated via acetate.…”
Section: Concentration Pulse Responses Under Closed Circuit Potentiosmentioning
confidence: 99%
“…showing that a direct electrooxidation of proprionate is possible. On the other hand, Hari et al (2016) suggested that current from propionate would be generated via acetate.…”
Section: Concentration Pulse Responses Under Closed Circuit Potentiosmentioning
confidence: 99%
“…Thus, they were observed to potentially play both roles in the community. The exoelectrogens-fermenter synergy results from cross-feeding of intermediates (Zeng et al, 2017;Lewis et al, 2018), which has been reported by other groups illustrating the syntrophy in bioanode fed with other fermentable substrates as well (Freguia et al, 2007;Parameswaran et al, 2009;Kiely et al, 2011;Hari et al, 2016b). Use of a complex substrate such as BOAP in a bioanode results in a complex web of microbial interactions as shown in Figure 5.…”
Section: Bioelectrochemistry Of Primary Reactions Leading To Electroamentioning
confidence: 55%
“…Amplicon libraries were prepared for the archaeal and bacterial 16S rRNA gene V3–V4 region using up to 10 ng of the extracted DNA, the forward primer Pro341F (5′-CCTACGGGNBGCASCAG-3′) and the reverse primer Pro805R (5′-GACTACNVGGGTATCTAATCC-3′) (Hari et al, 2016). Each PCR reaction (25 μL) contained dNTPs (100 μM of each), MgSO 4 (1.5 mM), Platinum Taq DNA polymerase HF (0.5 U/reaction), Platinum High Fidelity buffer (1x) (Thermo Fisher Scientific, United States) and tailed primer mix (400 nM of each forward and reverse primer).…”
Section: Methodsmentioning
confidence: 99%